HPC Parallelisation of Boundary Conditions in Multiscale Methods. Issue 4 (December 2014) - Asproulis, Nikolaos; Drikakis, Dimitris
This paper investigates two numerical implementations of continuum boundary conditions in parallel high performance computing (HPC) systems in conjunction with multiscale modelling comprising molecular dynamics (MD) and computational fluid dynamics (CFD) methods. The multiscale method provides the best compromise in terms of accuracy and computational cost in mesoscale regimes, however, there are still algorithmic challenges preventing the practical application of these methods. The present study investigates some of these challenges, namely different domain decompositions of the momentum transferred from the continuum domain to the atomistic region in conjunction with HPC parallelisation.